POLA PEMANFAATAN AIR SUNGAI DARI DAM ALAMI WAE ELA UNTUK MASYARAKAT - Patty, Farhani Amalia; Nanlohy, W. D.; Ruman, Rifyan (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The availability of clean water following the Wae Ela natural dam landslide disaster has become a crucial challenge for the people of Negeri Lima due to the damage to vital infrastructure. This study aims to analyze the water utilization patterns of the Wae Ela river and its determinants using qualitative methods with an exploratory case study design. Through in-depth interviews and observations, it was found that the utilization patterns are adaptive but very limited, where 100% of the community only uses water for non-consumptive domestic needs such as bathing and washing. Quantitative data shows an average usage volume of 130 liters per individual per visit with a dominant frequency of 2-3 times a week, concentrated in the morning (46.6%) and afternoon (33.3%). This pattern is hierarchically influenced by five main factors: the lack of adequate infrastructure, physical accessibility constraints, competition with alternative water sources, socio-economic stratification, and institutional gaps. It is concluded that current water utilization is highly dependent on individual physical and economic access without an equitable distribution mechanism, thus urgently requiring sustainable water governance policy interventions. ABSTRAK Ketersediaan air bersih pascabencana longsor bendungan alami Wae Ela menjadi tantangan krusial bagi masyarakat Negeri Lima akibat kerusakan infrastruktur vital. Penelitian ini bertujuan menganalisis pola pemanfaatan air sungai aliran Wae Ela dan faktor determinannya menggunakan metode kualitatif dengan desain studi kasus eksploratif. Melalui wawancara mendalam dan observasi, ditemukan bahwa pola pemanfaatan bersifat adaptif namun sangat terbatas, di mana 100% masyarakat hanya menggunakan air untuk kebutuhan domestik non-konsumsi seperti mandi dan mencuci. Data kuantitatif menunjukkan rata-rata volume penggunaan sebesar 130 liter per individu per kunjungan dengan frekuensi dominan 2-3 kali seminggu, yang terkonsentrasi pada waktu pagi (46,6%) dan sore hari (33,3%). Pola ini dipengaruhi secara hierarkis oleh lima faktor utama, yaitu ketiadaan infrastruktur memadai, kendala aksesibilitas fisik, kompetisi dengan sumber air alternatif, stratifikasi sosial-ekonomi, serta kekosongan kelembagaan. Disimpulkan bahwa pemanfaatan air saat ini sangat bergantung pada kemampuan akses fisik dan ekonomi individu tanpa mekanisme pemerataan, sehingga mendesak perlunya intervensi kebijakan tata kelola air yang berkelanjutan.